PECULIARITIES OF STRUCTURE-FORMATION AT SVS IN MELTED CONDENSED MIXTURES AT INFLUENCE OF CENTRIFUGAL FORCE - V. V. Hubovich; M. M. Kulak; V. G. Samoletov (Литьë и металлургия)
The influence of centrifugal force on dynamics of the burning wave spread and the carbide particles distribution in metallic alloy in the process of SVS-casting is considered. It was concluded that centrifugal force can be used for production of materials with gradient of the hardening particles concentration.